Analysis of Heavy Metals Concentration in Soil and Litchens from Various Localities of Hosur Road, Bangalore, India - Abida Begum; M. Ramaiah; Harikrishna; Irfanulla Khan; K. Veena (E-Journal of Chemistry)
Assessment of heavy metal content in litchens and soil samples from various localities of Hosur Road, Bangalore south was undertaken. Topsoil samples (0-10 cm) were taken at various locations, the metals analysed were Cr, Pb, Fe, Zn, Ni and Cu. The geoaccumulation index of these metals in the soils under study residential areas indicated that they are uncontaminated with Ni, Zn, and Fe and moderately contaminated with Cr and Pb. In Industrial areas and traffic junctions the concentration of Fe, Pb and Ni was maximum. Heavy metal accumulation in few prominent lichens of some localities was analysed. Cr and Pb were maximum in Chrysothrix candelaris (L.) Laundon, at the gardens of Madiwala and Silk Board junction with 95.29 and 623.95 µg g–1 dry weight respectively. Fe and Cu were maximum in Bulbothrix isidiza (Nyl.). Hale and Pyxine petricola Nyl at Central Prison campus and Kendriya Sadan campus with 22721 and 338.12 µg g–1 dry weight respectively, Lecanora perplexa Brodo at Infosis and Wipro Campus, electronic city have 531.5 and 634 µg g–1 dry weight of Zn. While Ni and Fe were maximum in Arthopyreniaceae at Shanti Niketan of MICO Limited with 1100 and 23200 µg g–1 dry weight respectively.